Frequency and Comparison of Personality Types of Pre-Medical and First-Year Medical Students in Choosing Medicine as a Career Choice and its Association with the Education System and Socioeconomic Status - Rafiq, Ayesha; Sethi, Ahsan; Sajjad Khan, Najia; Rafiq, Anam (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the frequency and compare personality types among pre-medical and first-year medical students and their relation to the education system and socioeconomic status.Study Design: Comparative cross-sectional study.Place and Duration of Study: Ayub Medical College, Abbottabad and three Secondary-Level Institutes of Abbottabad, Pakistan, from Jan to Mar 2020.Methodology: Of 384 students, 192 were each included in pre-medical and first-year medical groups. After obtaining written informed consent, data was collected on a questionnaire based on the Myers-Briggs Type Indicator. Socioeconomic status was assessed using a modified Kuppuswamy scale.Results: Common personality types among pre-medical students were extrovert-intuitive-feeling-perceiving 33(17.2%), extrovert-intuitive-feeling-judging 22(11.5%), and introvert-intuitive-feeling-judging 19(9.89%), while among medical students, common types were extrovert-intuitive-feeling-perceiving 34(17.7%), extrovert-intuitive-feeling-judging 25(13%), introvert-intuitive-feeling-perceiving 21(10.9%) and extrovert-sensing-feeling-judging 21(10.9%). Pre-medical and medicalstudents have attitude preferences towards extroverts, intuitive, feeling, and perceiving. A greater inclination for feeling was found among medical students than pre-medical and for perceiving among pre-medical students than medical. For paired personality preferences, both groups have expressed a predilection for intuitive feeling and feeling perceiving. Comparison between groups was statistically insignificant (p=0.788). There was a statistically insignificant difference between personality types with the education system in the pre-medical (p=0.058) and medical group (p=0.916) and with socioeconomic status in the pre-medical (p=0.146) and medical group (p=0.931).Conclusion: Pre-medical and medical students shared similar personalities. Identifying personalities at the pre-medical level is important so medical students find synchronisation between their personalities and studies. Socioeconomic status should also be considered.